Early combined immunosuppression for the management of Crohn's disease (REACT): a cluster randomised controlled trial. Issue 10006 (7th November 2015) - Khanna, Reena; Bressler, Brian; Levesque, Barrett G; Zou, Guangyong; Stitt, Larry W; Greenberg, Gordon R; Panaccione, Remo; Bitton, Alain; Paré, Pierre; Vermeire, Séverine; D'Haens, Geert; MacIntosh, Donald; et al.
Summary: Background: Conventional management of Crohn's disease features incremental use of therapies. However, early combined immunosuppression (ECI), with a TNF antagonist and antimetabolite might be a more effective strategy. We compared the efficacy of ECI with that of conventional management for treatment of Crohn's disease. Methods: In this open-label cluster randomised controlled trial (Randomised Evaluation of an Algorithm for Crohn's Treatment, REACT), we included community gastroenterology practices from Belgium and Canada that were willing to be assigned to either of the study groups, participate in all aspects of the study, and provide data on up to 60 patients with Crohn's disease. These practices were randomly assigned (1:1) to either ECI or conventional management. The computer-generated randomisation was minimised by country and practice size. Up to 60 consecutive adult patients were assessed within practices. Patients who were aged 18 years or older; documented to have Crohn's disease; able to speak or understand English, French, or Dutch; able to access a telephone; and able to provide written informed consent were followed up for 2 years. The primary outcome was the proportion of patients in corticosteroid-free remission (Harvey-Bradshaw Index score ≤4) at 12 months at the practice level. This trial is registered withClinicalTrials.gov, numberNCT01030809 . Findings: This study took place between March 15, 2010, and Oct 1, 2013. Of the 60 practices screened, 41 were randomly assigned to either ECI (n=22) or conventional management (n=19). Two practices (one in each group) discontinued because of insufficient resources. 921 (85%) of the 1084 patients at ECI practices and 806 (90%) of 898 patients at conventional management practices completed 12 months follow-up and were included in an intention-to-treat analysis. The 12 month practice-level remission rates were similar at ECI and conventional management practices (66·0% [SD 14·0] and 61·9% [16·9]; adjusted difference 2·5%, 95% CI −5·2% to 10·2%, p=0·5169). The 24 month patient-level composite rate of major adverse outcomes defined as occurrence of surgery, hospital admission, or serious disease-related complications was lower at ECI practices than at conventional management practices (27·7% and 35·1%, absolute difference [AD] 7·3%, hazard ratio [HR]: 0·73, 95% CI 0·62 to 0·86, p=0·0003). There were no differences in serious drug-related adverse events. Interpretation: Although ECI was not more effective than conventional management for controlling Crohn's disease symptoms, the risk of major adverse outcomes was lower. The latter finding should be considered hypothesis-generating for future trials. ECI was not associated with an increased risk of serious drug-related adverse events or mortality. Funding: AbbVie Pharmaceuticals.